New marketing strategies for online group-buying business from a social interaction theory perspective - Jiang, Lu; Huang, Yu; Zhu, Hong; Zou, Yingru (Frontiers in Psychology, 2022)
Companies that use online group-buying to get new business expansion opportunities at a price advantage are failing. Therefore, there is a need to develop new marketing strategies for group-buying companies to achieve market share and consumer favor. Given that consumers are society members, we used the social interaction theory to investigate the combination of factors that stimulate consumers’ purchase intentions. Fuzzy-set Qualitative Comparative Analysis was performed to evaluate different strategy configurations of social interaction elements, perceived quality, benefits and trust to promote purchase decisions from 406 group-buying consumer questionnaires. We revealed four pathways with different configurations that can prompt consumers to make group-buying decisions: information strategy, Word-of-Mouth strategy, sense of community strategy, as well as combining Word-of-Mouth and sense of community strategy. These strategies provide viable approaches through which group-buying companies can rationally use marketing programs to promote consumers’ purchase intentions.